Telessaúde Sergipe: main demands of the professionals of the oral health (Research, Society and Development, 2021)
The implementation of the Teleodontology Program in the State of Sergipe began in 2012 in partnership with the Ministry of Health, covering the 75 municipalities in Sergipe with access points present in Primary Health Care units and clinics. Currently, the Sergipe Teleodontology Center contemplates 100% of the state's municipalities with 163 points in place. Thus, the present study aimed to identify the demands sent by dental surgeons from the State of Sergipe to Telehealth in the period from 2013 to 2019. Data werecollected from Teleodontology databases, containing information from 230 registered professionals, totaling a sample. of 137 doubts. Among the doubts, approximately 30% are about diagnosis, followed by 13% about the type of medication, mainly related to groups such as pregnant women and hypertensive patients. Among the municipalities that use the tool, the most are Aracaju and Nossa Senhora do Socorro. There is a gradual use by professionals, being in the year 2013 to 2014 with only 27 questions. There was great adherence by the use of the tool by professionals, assisting in the process of better service to the population and diagnoses based on references from the Ministry of Health.